Comparison of nutrients and ultra-processed food consumption between different phenotypes defined by abdominal obesity and sarcopenia - Jang, Eunjin; Jeong, Sarang; Kim, Jinhyun; Jung, Sukyoung; Kim, Jee Young; Lee, Jung Eun; Park, Sohyun; Son, Jang Won, On behalf of the GOMS study group, Korean Society for the Study of Obesity (Frontiers in Nutrition, 2026)
BackgroundObesity, sarcopenia, and sarcopenic obesity require effective nutritional strategies in public health.MethodsThis cross-sectional study analyzed 535 adults aged 40–60 years in rural Korea. Participants were grouped by abdominal obesity (waist circumference ≥90 cm for men, ≥85 cm for women) and probable sarcopenia (handgrip strength ≤28 kg for men, ≤18 kg for women). Dietary intake was assessed using a semi-quantitative food frequency questionnaire and NOVA classification. Associations between food group intake and each phenotype were analyzed using multinomial logistic regression, adjusting for confounders.ResultsCompared with healthy controls, the probable sarcopenia group reported lower intakes of total protein (p = 0.041), vitamin A (p = 0.041), and carotenoids (p = 0.046), and higher intake of processed culinary ingredients (p = 0.012). The sarcopenic obesity group had lower intake of minimally processed foods (p = 0.046) and higher intake of ultra-processed foods (p = 0.010). In regression models, higher protein intake was associated with lower odds of probable sarcopenia (OR = 0.73, 95% CI: 0.56–0.95). Higher ultra-processed food intake was associated with increased odds of abdominal obesity (OR = 1.26, 95% CI: 1.03–1.54) and sarcopenic obesity (OR = 1.37, 95% CI: 1.02–1.84).ConclusionHigher protein and minimally processed food intakes were associated with lower odds of probable sarcopenia, whereas higher ultra-processed food intake was associated with higher odds of abdominal and sarcopenic obesity in middle-aged adults in rural Korea. These observational findings may inform hypothesis generation and public health planning, but prospective studies are needed to confirm these associations and assess causality.